The first record of amphibians as paratenic hosts of Serpinema larvae (Nematoda; Camallanidae) - Gonzalez, Cynthya Elizabeth (2007)
Lysapsus limellum Cope, 1862  is a member of the frog family Hylidae. It is distributed exclusively in South America, in Uruguay, Paraguay, Bolivia and the north of Argentina. In Argentina, L. limellum is restricted to some areas adjacent to the Paraguay and Paraná rivers. It shows a great preference for aquatic habitats, and occurs in permanent and semipermanent ponds. Studies on the parasite fauna of L. limellum from Corrientes, Argentina showed the presence of thirty three nematode larvae of the family Camallanidae. Specimens were identified as third-stage of Serpinema cf. trispinosum. The present report represents the first record of Serpinema larvae in amphibians, and suggests the importance of amphibians as paratenic host of freshwater turtle parasites. The genus Serpinema is registered by the first time in Argentina